Working Paper 15: Tracking and tracing stolen assets in foreign jurisdictions (Basel Institute on Governance Working Papers, 2013)
It has been estimated that roughly 1.6 trillion USD in criminal proceeds are laundered through the international financial system each year. To put this in perspective, this sum is more than the combined GDPs of Switzerland, Portugal, Romania, Belarus, and Austria in 2011.To enjoy this unnerving amount of illicit assets, criminals are forced to launder these funds through legitimate international financial channels in an attempt to disguise their illegitimate origins. Consequently, if an investigator knows how and where to look, there is always a connection that links a criminal’s assets to his or her crimes – and if sufficient evidence of this connection can be shown, then law enforcers can use it to successfully take legal action and return the assets to the victims of their crime.This paper appeared in eucrim, the European Criminal Law Associations’ Forum, 2013/2, published by Max Planck Society for the Advancement of Science, c/o Max Planck Institute for Foreign and International Criminal Law, Freiburg i. B., Germany.
Keywords: asset recovery; anti-money laundering; illicit funds; financial investigation